Desa Wisata competitiveness in the national tourism strategic Area (KSPN), Jerowaru; A case study of pare mas Lombok Timur - Mugni Mugni; Made Murdana (International Journal on Social Science, Economics and Art, 2023)
Desa Wisata has become a super priority for economic development in rural areas today. As a locomotive driving the economy, Desa Wisata must transform into a superior-tourist-venues to accelerate and create independent economic opportunities for villages. Therefore, this study aims to map the variety of Desa Wisata competitiveness in the national tourism strategic area (KSPN), Pare Mas Jerowaru Kabupaten Lombok Timur, by adopting qualitative descriptive research as its approach. We randomly chose Pare Mas as the research location because the profiling data of Desa Wisata in national tourism strategic areas is homogeneous. We administer focus group discussions (FGD) with managers, village officials and Pokdarwis for the data collection process and through interviews and observation of participants at the research location. The findings show that Pare Mas is a superior Desa Wisata with natural potential spread over two central potentials: coastal potential and mangrove forests. Meanwhile, plastic pollution in the sea, mangrove tree felling and increased industrial development in Pare Mas Village can threaten the existence of existing tourism potential.